Assessing Qualitative Studies in Public Administration Research. (7th September 2017) - Ospina, Sonia M.; Esteve, Marc; Lee, Seulki
Abstract : Systematic reviews of research methods in the public administration field have assessed the progress of research practice and offered relevant recommendations to further develop research quality. But most recent reviews examine quantitative studies, and the few assessments of qualitative scholarship tend to focus on specific dimensions. This article calls attention to the overall practice of qualitative research in the field of public administration. The authors analyzed 129 qualitative studies published during a five‐year period (2010–14) in the six top public administration journals, combining bibliometric and qualitative analyses. Three findings are drawn from the analysis. First, qualitative work represents a very small percentage of the journal articles published in the field. Second, qualitative research practice uses a small range of methodologies, mainly case studies. Finally, there is inconsistency in reporting methodological decisions. The article discusses the implications of these findings and offers recommendations to ensure methodological rigor while considering the integrity of the logic of inquiry and reporting standards of qualitative research practice .